The learning methods of Kulintangan among Orang Sungai community in Sabah / Elqabukhaemi Norafieqah Darwis - Elqabukhaemi Norafieqah, Darwis (Faculty of Music, 2017)
The purpose of this study is to investigate the learning methods used for Kulintangan among Orang Sungai Community in Sabah‘ This study is focusing on two elements which are to find types of learning methods and playing techniques on Kulintungun. Qualitative method was used in conducting this research through interviews which were done on 10 selected musicians who have played Kulintangan in Sabah. This research is hope to provide different approaches which can be used and suited for younger generation in playing the Kulintangan.